Uma crítica à Teoria Tridimensional do Direito de Miguel Reale : Nietzsche e a matemática transreal como possibilidades para um direito na imanência - Florêncio, Gilbert Ronald Lopes (2019)
The so-called Tridimensional Theory of Right (TTD), presented by the jusphilosopher Miguel Reale, bases its bases on the dialectical interaction of implication, complementarity, normative (abstract normativism: validity), phatic (legal sociology: efficacy) and axiological (legal moralism: fundamentals), in such a way that, due to the social dynamics and the new values resulting from this dynamic, the fact is valued, and then the norm applicable to the particular case submitted to judgment is revealed, with special emphasis on the occurrence of a surprising phenomenon, that in the words of Reale himself, "without suffering any graphic change", "the text of the law (legislated law), "without having any alteration of a comma, means something else." Thus, this is the crux of the criticism sought in this work, namely, to demonstrate that TTD, in that it opens the possibility for the magistrate to revalue the norm legislated to the point of even promoting a rupture with the meaning of its text and, thus breaking away, ends up allowing, albeit unintentionally, the empire of solipsism and the axiological idiosyncrasies of the judge, who sometimes distances himself from the moral north set by the legislator, so as to situate the judge in a plan of superior ethical capacity, i.e., of moral reflection, which constitutes a serious misunderstanding, since it leads to the production of dissonant norms of application of the social model advocated, in the immanence of the legislative process, by those who, in a representative Democracy, are the legitimate representatives of society. Thus, the act of judgment becomes, in fact, an idiosyncratic moral choice of each judge, from which inexorable and relevant unpredictability derives from the applicable law and, consequently, legal uncertainty, since the criteria of ideality) will not necessarily be in line with that prevailing in a given society, and therefore, they will appear detached from the desired reality (social model intended), establishing a scenario that in no way contributes to the primary function of Law that is the social pacification, being such a conclusion reached through the analysis of the Nietzschean thought, being the Transreal Mathematics brought to this dissertation, then, as imaginary resource to demonstrate all this exposed scenario.